Internalisasi Multikulturalisme dalam Pendidikan Islam - Julaiha, Siti (Dinamika Ilmu, 2014)
Human and humanity are positive and optimistic. In Islam, all human come from one source; Nabi Adam and Hawa. Although, human is from the same ancestor, but then they are flourishing into different races, tribes, or nations, with all different cultures and way of life. Those differences provoke them know others and appreciate others. This is, then, called “universal humanity” perspective by Islam that will determine and push the solidarity among others. Multiculturalisme-paradigmed education or multicultural education in Islamic education has been applying for many years. It just need to reform and reinforce, so the Islamic education practitioners realize it and implement it in the all level of Islamic education. Multicultural education has inherently established since the birth of Indonesia, as wellknown of Bhineka Tunggal Ika, gotong royong, helpful, and appreciate others. That is a huge foundation to improve the quality of Islamic multicultural education bigger and bigger. This paper proposes some ideas in internalizasing the Islamic multicultural education.